Molecules and Functions of Cornus officinalis Bark Volatiles - Peng, Wanxi (Emirates Journal of Food and Agriculture, 2018)
Cornus officinalis Sieb. et Zucc is a traditional Chinese valuable medicinal material. Clinically, it is customary to use ripe fruits from which seeds have been removed for medicinal purposes. The pulp contains 16 amino acids and a large number of essential elements for the human body. In recent years, with the expansion of the application of cornus officinalis, its pharmacological and pharmacological effects have been increasingly studied. At present, significant achievements have been made in the study of the bioactive components of cornus officinalis. The research of these achievements has been based on the research of the fruit of cornus officinalis. The study of branches or bark of cornus officinalis is very rare. With the fruit of cornus officinalis getting more and more attention, in order to solve the problem of the shortage of cornus officinalis fruit in the market, in this paper, starting from the study of bark of cornus officinalis, TGA-DTG and PY-GC-MS analysis methods were used to study the weight loss and pyrolysis of cornus officinalis bark, providing a basis for more fully utilizing cornus officinalis resources. With reference.